2017
DOI: 10.13005/bbra/2562
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eight Weeks of Aerobic, Anaerobic and Resistance Training on some factor of Endocannabinoid System, Serotonin, Beta-Endorphin and BDNF in Young Men

Abstract: The aim of this study was investigated the effect of eight weeks of aerobic, anaerobic and resistance training on some endocannabinoid, serotonin, beta-endorphin and BDNF agents of young men. Thirty-two young men (19 to 25 years old) who did not have regular physical activity were randomly divided into four groups, and each of them were participated in various sports exercises for eight weeks. A group for aerobic exercises (two exercises with 65-70 maximum heart rate 3 sessions per week), an anaerobic exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Aerobic performance significantly improved serotonin levels, whereas no improvements for anaerobic or strength physical activity have been observed. This could be the explanation for these results [ 64 ].…”
Section: Discussionmentioning
confidence: 92%
“…Aerobic performance significantly improved serotonin levels, whereas no improvements for anaerobic or strength physical activity have been observed. This could be the explanation for these results [ 64 ].…”
Section: Discussionmentioning
confidence: 92%
“…Both 5-HT and oxytocin are found in the insular cortex [ 59 , 60 ]. Some studies report that 5-HT increases in participants who experience exercise-induced euphoria [ 61 , 62 ]. In addition, intranasal administration of oxytocin boosts participants’ experience of specific positive emotions during meditation [ 63 ], and saliva oxytocin levels increase during meditation [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Tsutsumi et al, 1997) indicated that both the high resistance programs and low density have a significant role in improving fitness and psychological performance. (Hamedinia et al, 2017) also indicated that resistance exercises have a positive influence on serotonin hormone secretion, but this study did not define the intensity that the study sample has practiced.…”
Section: The Impact Of Somementioning
confidence: 90%